PENGARUH PENDAPATAN PEMBIAYAAN MURABAHAH, MUDHARABAH TERHADAP PROFITABILITAS PADA BANK RAKYAT INDONESIA (BRI) SYARIAH - Lusiana Kanji (Jurnal Unicorn ADPERTISI, 2022)
LUSIANA KANJI (2011) The effect of murabahah and mudharabah financing income on profitability at BRI Syariah banks. This study aims to determine the effect of murabahah, mudharabah financing income on profitability at BRI Syariah banks. Data collection uses secondary data obtained from the website https://www.ir-bankbsi.com. By using the saturated sampling technique. The population is BRI sharia bank while the sample taken is 36 from the monthly report of BRI sharia bank for the period 2017-2019. The results of the data and in the form of normality test, multicollinearity test, heterokedessity test. The data analysis method used multiple linear regression with the help of SPSS software. The results showed that murabahah and mudharabah financing had no effect on profitability.